2021
DOI: 10.1101/2021.11.27.21266942
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outcomes of Anti-Spike Monoclonal Antibody Therapy in Pregnant Women with Mild to Moderate COVID-19

Abstract: ObjectiveTo evaluate the efficacy and safety of anti-spike monoclonal antibodies (MAb) in the treatment of mild to moderate COVID-19 in high-risk patients who are pregnant.MethodsThe database of patients treated with monoclonal antibodies in the Mayo Clinic Midwest region was reviewed for patients who were pregnant at the time of infusion. Manual chart review was performed to collect demographic details as well as COVID course for both the mother and the infant if delivered. The data are presented using descri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…3 Thilagar et al (preprint) reported outcomes of 51 pregnant patients treated with antispike mAbs for COVID-19 infection. The mean maternal age was 31.1 y and mean gestational age was 180.1 d. No fetomaternal complications were reported and 29 patients had healthy babies 4 (Table 1).…”
mentioning
confidence: 98%
“…3 Thilagar et al (preprint) reported outcomes of 51 pregnant patients treated with antispike mAbs for COVID-19 infection. The mean maternal age was 31.1 y and mean gestational age was 180.1 d. No fetomaternal complications were reported and 29 patients had healthy babies 4 (Table 1).…”
mentioning
confidence: 98%